Prevalence of ocular disease during dupilumab treatment for atopic dermatitis: a bicentric retrospective comparative cohort study. (26th May 2021) - Barbé, Jordane; Poreaux, Claire; Remen, Thomas; Schoeffler, Amélie; Cloché, Véronique; Schmutz, Jean‐Luc; Escobar, Gabriela; Busztejn, Anne‐Claire
Abstract: Background: Dupilumab is the first human monoclonal antibody approved for the treatment of atopic dermatitis (AD). Clinical trials have reported an increase of ocular side effects in patients who receive dupilumab, with a prevalence of 5–37%. Objective: To compare the prevalence of ocular disease between AD patients receiving dupilumab treatment and AD reference group and to study the profile of the patients who developed ocular disease secondary to dupilumab treatment. Methods: Efficacy outcomes were collected both at baseline and at month 4 (M4). Presence of ocular disease was recorded at M4. Results: Data from 100 patients were examined. At M4, ocular disease was significantly more frequent in the dupilumab group (36% vs. 10%, P  = 0.002). Severe allergic conjunctivitis and blepharitis were significantly more frequent in the dupilumab group (30% vs. 4%, P  < 0.001, and 22% vs. 2%, P  = 0.004, respectively). Six of 18 patients permanently discontinued therapy. Conclusion: This study observed a prevalence of 36% of ocular disease in AD patients treated with dupilumab. Additional studies are required to confirm the risk factors we found for dupilumab‐associated ocular disease and to identify new ones. Consultation with an ophthalmologist before the introduction of dupilumab might limit the occurrence of complications.